2021
DOI: 10.1016/j.ejrad.2021.109531
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocal communication of pericoronary adipose tissue and coronary atherogenesis

Abstract: Pericoronary adipose tissue (PCAT) has been linked to underlying coronary artery disease (CAD) and proposed to modulate adjacent atherosclerotic plaque formation over pro-inflammatory pathways. In vitro and ex vivo studies support the bilateral communication of adipose tissue and vessel wall. We quantified PCAT and its dynamics in a low coronary risk cohort with a semi-automated software in serial coronary computed tomography angiography (CTA). Methods: We retrospectively included patients from a tertiary care… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Hoshino et al [ 40 ] mentioned that FAI was associated with cardiac mass, and some studies have reported a correlation between LV function and EAT [ 51 , 52 ]; notably, these results are similar to ours. In addition, studies have shown that LV dysfunction and increased FAI (> 70.1 HU) can significantly increase the cardiac mortality [ 42 , 53 ]. Our results suggest that cardiac mortality caused by increased FAI may be due to changes in LV function.…”
Section: Discussionmentioning
confidence: 99%
“…Hoshino et al [ 40 ] mentioned that FAI was associated with cardiac mass, and some studies have reported a correlation between LV function and EAT [ 51 , 52 ]; notably, these results are similar to ours. In addition, studies have shown that LV dysfunction and increased FAI (> 70.1 HU) can significantly increase the cardiac mortality [ 42 , 53 ]. Our results suggest that cardiac mortality caused by increased FAI may be due to changes in LV function.…”
Section: Discussionmentioning
confidence: 99%
“… 13 , 14 Pericoronal adipose tissue-FAI can be regarded as a quantitative index of PCAT density changes; many studies believe that it has a certain relationship with major adverse cardiac events (MACEs) and that it can be used as a standard to measure the changes of perivascular inflammatory microenvironment. 15 , 16 It is believed that EAT may be related to the progression of coronary atherosclerotic plaque, but there are few studies related to the relationship between PCAT and coronary atherosclerosis. Therefore, this study got rid of the exploration of EAT.…”
Section: Discussionmentioning
confidence: 99%
“…This may be because coronary artery and myocardium has no obvious boundary, and the PCAT can release cytokines reach myocardium and coronary artery through paracrine signaling mechanisms, which results in the changes of myocardial and left ventricular function [34] . In addition, studies have shown that left ventricular dysfunction and increased FAI (> 70.1HU) can signi cantly increase the cardiac mortality [31,35] . Our results suggest that cardiac mortality caused by increased FAI may be due to changes in left ventricular function.…”
Section: Discussionmentioning
confidence: 99%